Ploidy and clinical characteristics of childhood acute myeloid leukemia: A NOPHO‐AML study. Issue 8 (18th April 2014) - Sandahl, Julie Damgaard; Kjeldsen, Eigil; Abrahamsson, Jonas; Ha, Shau‐Yin; Heldrup, Jesper; Jahnukainen, Kirsi; Jónsson, Ólafur G.; Lausen, Birgitte; Palle, Josefine; Zeller, Bernward; Forestier, Erik; Hasle, Henrik
<x xml:space="preserve">Abstract</x> We report the first large series (n = 596) of pediatric acute myeloid leukemia (AML) focusing on modal numbers (MN) from the population‐based NOPHO‐AML trials. Abnormal karyotypes were present in 452 cases (76%) and numerical aberrations were present in 40% (n = 237) of all pediatric AML. Among patients with an abnormal karyotype, the MN 46 was most common (n = 251; 56%) of which 36 (8%) were pseudodiploid with numerical aberrations, followed by MN 47 (n = 80; 18%) and MN 43–45 (n = 48; 8%). No cases had MN less than 43. Hyperdiploid AML with MN 48–65 comprised 11% of all cases and was associated with early onset (median age 2 years), female sex (57%), and a dominance of acute megakaryoblastic leukemia (AMKL) (29%). Hypodiploidy constituted 8% of all AML and was associated with older age (median age 9 years), male predominance (60%), FAB M2 (56%), and t(8;21)(q22;q22) (56%) with loss of sex chromosomes. Inferior outcome was observed for hypodiploid cases (5‐year event‐free survival 40% and 5‐year overall survival 40%) but did not reach statistical significance. Chromosomes were gained in a nonrandom pattern, where chromosomes 8, 21, 19, and 6 were the most commonly gained. In conclusion, based on MNs, two cytogenetic subgroups with characteristic clinical features are described; hypodiploidy found in 8% and associated with high median age, male sex, t(8;21)(q22;q22), and FAB M2 and possibly associated with inferior outcome (P = 0.13), and hyperdiploidy with MN 48–65 in 11% associated with early onset, female sex, and AMKL. © 2014 Wiley Periodicals, Inc.